Improving Students' Literacy and Numeracy Skills Theme of My Obligations and Rights through Problem Based Learning Model for Grade 3 Students of SD Negeri 2 Ngalas in the 2022/2023 Academic Year - Suryani, Suryani (Universitas Sebelas Maret, 2022)
This research aims to evaluate the impact of Problem-Based Learning (PBL) on improving the literacy and numeracy skills of third-grade students at SD Negeri 2 Ngalas, focusing on the theme